Young Durkheimians and the temptation of fascism: The case of Marcel Déat. (July 2015) - Desan, Mathieu Hikaru; Heilbron, Johan
In this article we assess the general claim that Durkheimian sociology has reactionary, fascist, or totalitarian affinities, and the specific claim that Marcel Déat's Durkheimian background was a significant factor in his becoming a Nazi sympathizer. We do so by comparing the different trajectories of the interwar generation of young Durkheimians and find that only one, i.e. Déat, can be said to have become fascist. Indeed, what characterizes this generation of Durkheimians is the variety of the ways in which they responded to the crises of the interwar years, both politically and scientifically. Nonetheless, most remained on the political left, and during the war many younger members of the Durkheimian group either fled the country or were involved in the French Resistance. As the only personal link between the Durkheimian group and fascism, Déat's career is of particular interest. Instead of Déat's being an orthodox Durkheimian, his successive engagements embody the intellectual fragmentation and heterodoxy characteristic of the interwar generation. We outline Déat's career by foregrounding the conjunctural and dispositional factors that we believe point toward a more plausible explanation of Déat's transformation than does an internalist history-of-ideas approach according to which his political evolution can be explained by reference to an underlying intellectual continuity. Déat's fascism is better explained by the repeated frustration of his political and intellectual ambitions that ultimately led to a fateful accommodation with Nazi power than by any tendency inherent to Durkheimian sociology.